Writing Instruction, Academic Labour, and Professional Development - Heidi Darroch; Micaela Maftei; Sara Humphreys (Discourse and Writing/Rédactologie, 2019)
As we envisioned this special section and, in turn, encouraged colleagues to contribute, we confronted one of the ironies of post-secondary writing instruction: many of the people entrusted with the responsibility of supporting student writing development are, essentially, excluded from professional conversations about effective writing pedagogy. That is, hired term-by-term, treated by their departments as fungible, and burdened with excessive teaching loads, university writing instructors may lack a sense of belonging to a profession or a discipline. College instructors, in turn, are also frequently precarious; even if working in full-time and permanent positions, they have little opportunity to engage with the profession, conducting research, as Brenna Clarke Gray points out, “off the sides of our desk.” The effect is a feeling of isolation and, for too many, despair about the sustainability of their work in higher education. This sentiment is expressed in the excellent work submitted by our contributors, who are each at differing points on their professional timelines, and, as a result, provide a range of viewpoints. We are grateful for their provocative and engaging work, and we also appreciate and acknowledge the formidable challenges of potential contributors who explained why they could not produce articles for publication--including some who struggled with how to represent their experience of academic precarity without hampering their employment prospects. We thank the editors of CJSDW/R for their patience and assistance as we completed this project amid other responsibilities.